2016
DOI: 10.3766/jaaa.15109
|View full text |Cite
|
Sign up to set email alerts
|

A Method for Assessing Auditory Spatial Analysis in Reverberant Multitalker Environments

Abstract: This new method appears to be useful for estimating spatial abilities in realistic multitalker scenes. The method is sensitive to the number of sources in the scene, and to effects of sensorineural hearing loss. Further work will be needed to compare this method to more traditional single-source localization tests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
19
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 29 publications
5
19
0
Order By: Relevance
“…Consistent with previous auditory enumeration studies (Kawashima & Sato, 2015;Weller et al, 2016;Zhong & Yost, 2017), we found that between three and four auditory objects could be enumerated with 50% accuracy. This was true when enumerating both spatially separated concurrent auditory objects in Experiments 1 and 2, and temporally separated sequential auditory objects in Experiment 3.…”
Section: Accurate (>50%) Auditory Enumeration Is Limited To Three To supporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with previous auditory enumeration studies (Kawashima & Sato, 2015;Weller et al, 2016;Zhong & Yost, 2017), we found that between three and four auditory objects could be enumerated with 50% accuracy. This was true when enumerating both spatially separated concurrent auditory objects in Experiments 1 and 2, and temporally separated sequential auditory objects in Experiment 3.…”
Section: Accurate (>50%) Auditory Enumeration Is Limited To Three To supporting
confidence: 91%
“…For example, Weller et al (2016) presented stimuli for up to 45 seconds and still found that normally-hearing listeners could only accurately identify up to four auditory sources.…”
Section: Accurate (>50%) Auditory Enumeration Is Limited To Three To mentioning
confidence: 99%
“…Localization of sounds in space is computationally challenging, particularly given the effects of reverberation in natural settings (Keating and King, 2015; Traer and McDermott, 2016), and likely relies on different underlying mechanisms than stream segregation (Snyder and Elhilali, 2017). The dissociation between utilization of spatial cues for the purpose of stream segregation and determining their specific spatial location is also supported by behavioral findings demonstrating increased sensitivity and discriminability for spatially segregated sounds, albeit with poor ability to report the spatial location of the target (Klatt et al, 2018; Middlebrooks, 2013; Weller et al, 2016). In other words, determining that two inputs originate from different locations is possible even when their exact location cannot be reliably discerned.…”
Section: Discussionmentioning
confidence: 81%
“…Moreover, the applied tasks need to be more realistic, address more cognitive processes, and provide visual cues as well as context information. For instance, speech comprehension may be measured by asking subjects to answer questions while listening to monologues or dialogues in a noisy environment (e.g., Best, Streeter, Roverud, Mason, & Kidd, 2016); and localization in quiet may be replaced by measures of auditory spatial awareness (e.g., Brungart, Cohen, Cord, Zion, & Kalluri, 2014 ; Weller, Buchholz, & Best, 2016 ). Finally, to draw stronger conclusions about the investigated processes within the implanted ears, the statistical power needs to be improved by applying more subjects.…”
Section: Discussionmentioning
confidence: 99%